Use of customised probiotics for western king prawn (Penaeus latisulcatus Kishinouye, 1896) culture - Ngo, Van Hai (Curtin University, 2009)
In recent decades, a rapid increase in fish production from the aquaculture sector has led to degradation of the environment due to indiscriminate use of chemical additives and veterinary medicines. Consequently, antimicrobial resistance among pathogenic bacteria has increased and environmental problems associated with these chemicals and antibiotics have become a burden for sustainable aquaculture development. Therefore, there is a need to alter the indiscriminate use of chemicals and antibiotics for the use in aquaculture by replacing these with prebiotics or other harmless substitutes. Different probiotics can confer huge functions and benefits to various hosts through the improvement in survival rates and enhancement of health. However, there is a need for special species-specific prebiotics in a particular culture environment.Customising the species-specific probiotics for prawn culture was performed via several experiments. After the specific prebiotics, Pseudomonas synxantha and P. aeruginosa were isolated and tested from a commercial product, the emphasis was on determining the effectiveness of them on the cultivation of the juveniles’ western king prawns, Penaeus latisulcatus. The customisation process began with trialling five inhibition test methods to determine the most effective detection method for the potential probiotic bacteria. P. synxantha and P. aeruginosa showed the highest inhibition against Vibrio spp. isolated from P. latisulcatus and pathogenic Vibrio isolated from other aquatic animals.A series of experiments were conducted under laboratory conditions to investigate the physiological and immune responses of the juvenile P. latisulcatus exposed to the customised probiotics. The research results proved the suitability of these probiotics for the cultivation of P. latisulcatus as they conclusively met all the essential requirements for the appropriate probiotics. The application of these customised probiotics at 10[superscript]5 CFU/mL as “water additives” or “feed supplements” improved the specific growth rate, survival and the health of juvenile P. latisulcatus. These customised probiotics showed similar beneficial effects as observed with other commercial prebiotics, Bio-Mos[superscript]® and ß-1,3-D-glucan. The supplementation of these probiotics with the formulated feed was more efficacious and more practical than direct application into the rearing media. The prawns exposed to the combined probiotics were healthier than those exposed to the individual probiotics. In addition, P. aeruginosa was more effective than P. synxantha for improving prawn health.P. latisulcatus were not adversely affected by the customised probiotics, as P. latisulcatus grew well in the presence of a high probiotic density of 10[superscript]7 CFU/mL. The application of the probiotics however, reduced the negative effects of the pathogen V. harveyi as the probiotic-fed prawns survived 100% when they were exposed to V. harveyi at 10[superscript]5, 10[superscript]7 and 10[superscript]3 CFU/mL for 24, 24 and 36 h, respectively. Hence customised probiotics are suggested as an alternative to antibiotic for disease control in prawn aquaculture. The prawn survival was also influenced by the concentrations of the pathogen and duration of the challenge. At a challengeconcentration of 10[superscript]3 CFU/mL of V. harveyi, the 100% survival-hours were shorter (12 h) in the control group (prawns not fed with probiotics) than in the probiotic-fed prawns (36 h). Further, prawns not fed with probiotics died at a faster rate (96 h) than the probiotic-fed prawns (156 h). The prawns died when the exposure to V. harveyi (even at 10[superscript]3 CFU/mL) was longer than 36 h. The probiotic-fed prawns could not completely resist the pathogenic effects of the V. harveyi despite the detection of the probiotics in the intestine of the prawns earlier than detection of V. harveyi. It is recommended that these customised probiotics can be used as a substitute to antibiotics in the cultivation of western king prawns.